Perceptions on Institutional Climate, School Coexistence and Teaching Strategies in Educational Institutions of Regular Basic Education in Nuevo Chimbote, 2024 - Villanueva Calonge, Zoila Rene (2024)
The objective of the research was to determine the relationship between perceptions, institutional climate, school coexistence and teaching strategies in educational institutions of regular basic education Nuevo Chimbote, 2024, the methodology was basic, the approach was quantitative, the design was non-experimental and correlational level of study, presenting a transversal scope, the population was made up of 3,586 teachers at the primary and secondary level of all new Chimbote; The sample was 200 subjects whose selection was made through nonprobabilistic, intentional sampling; The technique applied was the survey and three questionnaires were used as an instrument, thus determining a significant relationship (sig.=0.000<0.05) of the institutional climate with school coexistence (Rho=0.661) and teaching strategies (Rho=0.555). From these results, the conclusion was reached that there is a high and significant relationship between perceptions, institutional climate, school coexistence and teaching strategies, in addition, that the institutional climate stands as a pillar Fundamental in school coexistence and in the effective implementation of teaching strategies, a positive environment not only improves interpersonal relationships, but also enhances active learning and student participation.